Komparasi Return dan Risk Saham Syariah dan Konvensional di Bursa Efek Indonesia Periode 2020-2022 - Solatiyah, Baiq; Yakub, M (CV. Utility Project Solution, 2023)
This study aims to determine The difference between returns and risk on Islamic stocks and conventional stocks (a study on the Jakarta Islamic Index (JII) and LQ45 for the period 2020-2022). The study population is Islamic stocks listed in the Jakarta Islamic Index consisting of 30 issuers in each period and conventional shares listed in the LQ45 index which consists of 45 issuers in each period. Samples were taken as many as 7 shares listed in the Jakarta Islamic Index and 12 shares listed in the LQ45 index with a sampling technique using purposive sampling method. The data analysis technique used is descriptive statistics and inferential statistics by using a different test in drawing conclusions. Based on the normality test that has been done, the results show that the Jakarta Islamic Index and LQ45 return data is normality distributed and the Jakarta Islamic Index and LQ45 risk data are normally distributed. Based on the Independent Sample T Test obtained a significant value for the level of return > 0,05 which is equal to 0,931 and the level of risk < 0,05 which is equal to 0,014. So it can be concluded that, the return on Islamic stocks and conventional stocks are no difference. While the risk on Islamic stocks and conventional stocks are have difference.